2015
DOI: 10.1089/jcr.2014.0036
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Sleep in Adolescents: A Systematic Review

Abstract: Sleep restriction is prevalent during adolescence and is associated with a range of adverse outcomes, including daytime, academic, physical (e.g., hypercholesterolemia), and psychological (e.g., depression) impairments. Despite possessing sleep-disrupting properties and holding a central role in the modern adolescent diet, caffeine's potential as a contributing risk factor to the development of adolescent sleep restriction remains understudied. The current systematic review identified 16 papers investigating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 62 publications
1
5
0
2
Order By: Relevance
“…In consistent with other studies 3,4,[11][12][13][14][15] , it was also found that students consume a considerable quantity of caffeine on daily basis irrespective of the season (summer or winter). Tea (43%) is the top of caffeine source followed by coffee (29%) and cold drinks (22%).…”
Section: Variable Different Classes Of Medicalsupporting
confidence: 91%
“…In consistent with other studies 3,4,[11][12][13][14][15] , it was also found that students consume a considerable quantity of caffeine on daily basis irrespective of the season (summer or winter). Tea (43%) is the top of caffeine source followed by coffee (29%) and cold drinks (22%).…”
Section: Variable Different Classes Of Medicalsupporting
confidence: 91%
“…Further, the participants excluded from the present analyses (due to missing data) tended to use more substances and have later timing; consequently, the restricted range on these variables may have limited our ability to detect associations, thereby biasing the sample and increasing the likelihood of type II errors. Finally, our study did not assess patterns of caffeine use, which may be an important consideration in future studies given increasing use of energy drinks and evidence that caffeine use is associated with both sleep disturbances (Bonnar and Gradisar, ) and use of alcohol and other drugs (Arria et al., ; Choi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A second risk factor for insufficient sleep that has become equally prominent in recent years is the increasing popularity and consumption of energy drinks and other caffeinated drinks amongst adolescents [14,24], perhaps due to the youth-directed marketization of these products. Energy drinks often contain a moderate to high amount of caffeine, which has been linked to high blood pressure and sleep disturbances in children and adolescents [25].…”
Section: Psychoeducation To Improve Sleep Hygiene Amongst Adolescentsmentioning
confidence: 99%